Utilization of mobile apps among student with learning disability from Islamic perspective - Mohamed Zain, Nor Zuhaidah; Mahmud, Murni; Hassan, Azizzeanna (2013)
Living in a society in which information and communication technology (ICT) is so pervasive is quite challenging. The main purpose of this paper is to discuss the literature on use of mobile application technology for students with learning disability (SLD) in Malaysia environment from Islamic perspective. Mobile technology can offer appropriate educational environment to assist learning activities outside the classroom. Initial reading of Quranic verses indicated that people with disabilities are to be treated with full regard and to have the same subject-to-subject relations that are granted to the non-disabled. In Islam, a person’s worth is based not on any physical or material characteristics but on piety. Islam views disability as morally neutral. Throughout the world, disabled people are among the least privileged and most susceptible. Currently, use of mobile application facilities in Malaysian education system is still at early stage. It is hoped that more mobile application with Islamic knowledge will be developed in order to nourish positive value among SLD specifically and Muslim students generally.